Morphological operation on printed circuit board (PCB) reverse engineering using MATLAB - Che Mat, Ruzinoor; Azmi, Shahrul; Daud, Ruslizam; Zulkifli, Abdul Nasir; Ahmad, Farzana Kabir (Faculty of Information Technology, Universiti Utara Malaysia, 2006)
Image segmentation has been an important and challenging issue in the Feld of computer vision over decades. It ploys a critical role for most image analysis tasks, such as object detection and recognition.The aim of this paper is to obtain segmented image of Printed Circuit Board (PCB)'s track using mathematical morphological operation. Morphological image analysis is based on the idea that images represent a collection ofspatial paiterns that can be analyzed based on some prened parterns called structuring elements. Most basic morphological operation, dilation and erosion have been employed in this research. Detail elaboration on this method will be discussed and experimental results are presented.